1996
DOI: 10.1159/000259216
|View full text |Cite
|
Sign up to set email alerts
|

Forward Masking Is Dependent on Inner Hair Cell Activity

Abstract: The goal of this study was to test the hypothesis that the inner hair cell complex (inner hair cell and dendritic contacts) is solely responsible for generating the slope of the forward masking curve. To test this hypothesis two experiments were performed. The first was to measure forward masking from the Bronx waltzing mouse, a mutant possessing an inner hair cell defect. The Bronx waltzing mouse demonstrated an approximately 60-dB auditory brainstem response (ABR) threshold shift compared to CBA/CBA mice at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Experiments on mice, using auditory brainstem responses[17], have suggested that forward masking results indicate the status of the IHCs. After the offset of a noise burst the masking effect on a brief tone decreases rapidly in a good ear, but, according to that article, not in an ear with loss of IHCs.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments on mice, using auditory brainstem responses[17], have suggested that forward masking results indicate the status of the IHCs. After the offset of a noise burst the masking effect on a brief tone decreases rapidly in a good ear, but, according to that article, not in an ear with loss of IHCs.…”
Section: Methodsmentioning
confidence: 99%
“…), as described previously [16]. ABR measurements were performed immediately before and after operations.…”
Section: Assessments Of Auditory Functionmentioning
confidence: 99%
“…Therefore, the measurement of ABR has become a useful and practical procedure for the determination of hearing levels in animals and young children (Arnold, 2000;Musiek et al, 1994;Parham et al, 2001). In mice, the ABR threshold has been used successfully to estimate audiometric thresholds in hearing and genetic research (Davis et al, 2002;Duan and Canlon, 1996;Erway et al, 1996;Erway et al, 1993;Hirose and Liberman, 2003;Money et al, 1995;Munemoto et al, 1998;Rosowski et al, 2003;Szymko-Bennett et al, 2003). A PubMed search using key words of mouse, ABR, and threshold has revealed 80 of these studies since 1985.…”
Section: Introductionmentioning
confidence: 99%